2005
DOI: 10.1021/jf048934k
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and Antioxidant Properties of Milk−Kefir and Soymilk−Kefir

Abstract: This study was aimed at evaluating the antimutagenic and antioxidant properties of milk-kefir and soymilk-kefir. Such antimutagenic activity was determined by means of the Salmonella mutagenicity assay, whereas the antioxidant properties of kefir were evaluated by assessing the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activity, lipid peroxidation inhibition activity, ferrous ion chelating ability, reducing power, and antioxidative enzyme activity. Both milk-kefir and soymilk-kefir demonstrated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 56 publications
10
143
0
5
Order By: Relevance
“…It might also be because of the fact that it is used in the removal of free radicals produced after the lead accumulation in blood and tissues (Tandon et al, 2002). Studies done on antimutagenic and antioxidant properties of kefir have indicated that it has important effects on radicals and protects linoleic acid peroxidation (Liu et al, 2005). Dhawan et al, 1989 found that vit E eases the severity of lead toxication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It might also be because of the fact that it is used in the removal of free radicals produced after the lead accumulation in blood and tissues (Tandon et al, 2002). Studies done on antimutagenic and antioxidant properties of kefir have indicated that it has important effects on radicals and protects linoleic acid peroxidation (Liu et al, 2005). Dhawan et al, 1989 found that vit E eases the severity of lead toxication.…”
Section: Resultsmentioning
confidence: 99%
“…Yen, 1999a;b). I n a study designed on antimutagenic and antioxidative natures of kefir, it h a s been documented t o be a n important radical cleaner and inhibitor of lipid peroxidation (Liu et al, 2005). Although there are several natural and synthetic antioxidants available at present, there are various suspicions particularly on a long time usage effects and reliance of the synthetic ones.…”
Section: Introductionmentioning
confidence: 99%
“…According to Liu, Chen, and Lin, (2005), proteolysis may increase the concentration of carboxylic acid groups and an increased exposure of metal-chelating amino acid residues such as histidine. Hydrolysates obtained with Alcalase 1 , Flavourzyme 1 and sequential Alcalase 1 -Flavourzyme 1 of both legumes exhibit a greater chelating capacity, these enzyme systems probably generated more exposure of metal-chelating amino acid residues than the gastrointestinal enzymes Pepsin and Pancreatin.…”
Section: Chelating Of Metal Ions Fe 2þ and Cu 2þmentioning
confidence: 99%
“…Among the health benefits associated with kefir are: antimicrobial property and cicatrizing activity (Rodrigues et al, 2005), antimutagenic and antioxidant effect (Liu et al, 2005), hypocholesterolemic properties (Huang et al, 2013), betagalactosidase activity (Leite et al, 2013), anti-allergenic properties, anti-inflammatory activity, and stimulation of the immune system (Lee et al, 2007;Vinderola et al, 2006).…”
Section: Benefits Of Kefirmentioning
confidence: 99%